Choking under Pressure and Gender: Evidence from Professional Tennis - Danny Cohen-Zada; Alex Krumer; Mosi Rosenboim; Offer Moshe Shapir (Institute of Labor Economics (IZA), 2017)
We exploit a unique setting in which two professionals compete in a real-life tennis contest with high monetary rewards in order to assess how men and women respond to competitive pressure. Comparing their performance in low-stakes versus high-stakes situations, we find that men consistently choke under competitive pressure, but with regard to women the results are mixed. Furthermore, even if women show a drop in performance in the more crucial stages of the match, it is in any event about 50% smaller than that of men. These findings are robust to different specifications and estimation strategies.
Keywords: J16; J24; 330; gender; performance; competitive pressure; tennis; choking